Does human capital endowment of FDI recipient countries really matter? Evidence from cross-country firm level data - Sumon K. Bhaumik; Ralitza Dimova (Institute for the Study of Labor (IZA), 2012)
The stylized literature on foreign direct investment suggests that developing countries should invest in the human capital of their labour force in order to attract foreign direct investment. However, if educational quality in developing country is uncertain such that formal education is a noisy signal of human capital, it might be rational for multinational enterprises to focus more on job-specific training than on formal education of the labour force. Using cross-country data from the textiles and garments industry, we demonstrate that training indeed has greater impact on firm efficiency in developing countries than formal education of the work force.
urn:nbn:de:101:1-201206146574
Keywords: F23; I25; 330; human capital; training; firm-level efficiency; multinational enterprises; Direktinvestition; Multinationales Unternehmen; Wirtschaftliche Effizienz; Ausländisch; Humankapital; Betriebliche Ausbildung; Bildungsabschluss; Entwicklungsländer